The Development of Plant Conservation in Botanic Gardens and the Current and Future Role of Conservation Genetics for Enhancing Those Conservation Efforts - Christine E. Edwards (Molecular Frontiers Journal, 2019)
Botanic gardens play major roles in plant conservation globally. Since the 1980s, the number of botanic gardens worldwide and their involvement in integrating ex situ and in situ plant conservation has increased significantly, with a growing focus on understanding, documenting, and capturing genetic diversity in their living collections. This article outlines why genetic diversity is important for conservation, and explores how botanic gardens can establish and expand the use of molecular techniques to support their plant conservation efforts.